What is Ancient Political Thinking? - Bartninkas, Vilius (Problemos, 2019)
This paper examines the origins of ancient political thinking from (roughly) 750 to 348 B.C. The analysis of authors who had been discussing political questions over this period shows that ancient political thinking can be classified into three discourses: political thought, political theory, and political philosophy. The purpose of this paper is to define the characteristics of each discourse and to illustrate them with specific historical examples which show how these discourses interacted with the Greek political experiences and how political thought transformed into a theory and philosophy.
Keywords: Ancient philosophy; Political thought; Political theory; Political philosophy